PRAGMATIC STRATEGIES OF MALE AND FEMALE CUSTOMERS ON ONLINE CUSTOMER REVIEW AND RATING IN TOKOPEDIA - Rahayu, Anita; Djatmika; Nugroho, Miftah (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2025)
This research aims to analyze the pragmatic strategies of male and female customers while giving a nebulizer product review sold by Omron Healthcare in Tokopedia's online customer review and rating. The theories used in this research are gender and politeness strategies. This research is qualitative descriptive because the reality of the data depends on the context and is then described based on the context as well. The data source is in Tokopedia's online customer review, whereas the data are transcripts of male and female customers' comments on Omron Healthcare's nebulizer product. This research finds 50 data: 25 are male, and 25 are female customers. The findings show that male and female customers mostly use positive politeness while giving product reviews. However, females only use two sub-strategies of positive politeness, whereas males use four. Furthermore, the research finds that male customers use negative politeness strategies more often. Additionally, males use more off-record than females. Lastly, only males use the off-record strategy. In short, male and female customers give positive comments, but female customers use more hyperbolic expressions, while male customers use reciprocity and approval. Keywords: gender, online customer review, politeness strategy, pragmatics